Clinical and immunological variants of ANCA-associated systemic vasculitis: a look at the pulmonary fibrosis in microscopic polyangiitis with anti-myeloperoxidase antibodies and rheumatoid factor. Literature review and own observation - T. V. Beketova; O. A. Golovina; A. S. Avdeeva (Научно-практическая ревматология)
Depending on the epitope specificity of antineutrophil cytoplasmic antibodies (ANCA) and the presence or absence of a granulomatous inflammation. Patients with ANCA-associated vasculitis (AAV) show variability in clinical manifestations and prognosis depending on the epitope specificity of ANCA and the presence or absence of granulomatous inflammation. In this regard, it is important to identify the clinical and immunological phenotypes of AAV and a personalized approach to treatment. Microscopic polyangiitis (MPA) with antibodies to myeloperoxidase (aMPO) has a relatively high incidence of lung involvement and pulmonary fibrosis. We present our own clinical case of pulmonary fibrosis in MPA with aMPO and rheumatoid factor. Literature data are discussed. In cases of early arthritis and interstitial pneumonia, the possibility of AAV should be considered, a detailed examination is necessary to identify pathognomonic signs of AAV, including asymptomatic ones. Before prescribing immunosuppressants, the epitope specificity of ANCA should be determined. Treatment with rituximab, mycophenolate mofetil and nintedanib is discussed.